Alice's adventures in wonderland eaudiobook - Carroll, Lewis (Alice in Wonderland, 1980)
In 1862, during a boating party on the Thames River, a young Englishman named Lewis Carroll entertained three little girls by spinning a wondrous story of a disappearing cat, a mad tea party, and a croquet-playing Queen of Hearts. The story so enchanted one of the girls that she begged him to put it in writing. The result was overwhelming fame and fortune for the author and a beloved fantasy classic for children's literature. Alice's Adventures in Wonderland has captivated generations of children and adults with its unforgettable blend of laughter, magic and mischief. It is a hot summer afternoon when Alice spies a white rabbit hurrying across the riverbanks. "Oh dear! Oh dear! I shall be too late!" he cries, glancing at a watch drawn from his waist-coat pocket. Of course, Alice has never seen a rabbit wear a waist-coat or a watch before. Curious, she follows the creature-and plunges down a rabbit hole into a strange and unforgettable world.